PENERAPAN AKUNTANSI NIRLABA BERDASARKAN PSAK NO. 45 (STUDI KASUS PADA MASJID AL-BAITUL AMIEN DI JEMBER) - Desy Rustiyanti Rahayu; Moh. Halim; Gardina Aulin Nuha (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
This study aims to find out how financial management in mosques and see how the method of recording is related to the standards issued by the Indonesian Accounting Association (IAI) in financial reporting for non-profit organizations namely PSAK 45 at Al-Baitul Amien mosque in Jember. The author in conducting this research uses qualitative methods. Data collected by using interviews and documents by looking directly at the financial statements that have been presented by the mosque management. Interviews at the Al-Baitul Amien Mosque in Jember were conducted with the treasurer, financial staff and takmir of the mosque. The results of this study indicate that mosque administrators have managed finances openly as a form of accountability or financial accountability of the mosque by recording cash receipts and disbursements. Financial management is well recorded even though it is still simple. Regarding PSAK 45, mosque administrators have not recorded according to PSAK 45 because these standards are recognized as having never been heard and introduced to mosque administrators. Keywords: Mosque, PSAK No. 45, and SAK